2014
DOI: 10.1111/clr.12448
|View full text |Cite
|
Sign up to set email alerts
|

Are insertion torque and early osseointegration proportional? A histologic evaluation

Abstract: Reduced drilling dimensions resulted in increased insertion torque (primary stability). While BIC and BAFO were maximized when drilling the recommended diameter hole, only the oversized hole resulted in evidence of statistically reduced integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…A total of 591 implants were evaluated qualitatively: 348 installed with high insertion torque (. 25 Conclusion: The current review indicated that there is no significant difference in marginal bone resorption and implant failure rate between implants inserted with high or low insertion torque values. (Implant insertion torque, implant stability) to control implant healing and perform possible alterations in the treatment plan as a delayed load or progressive load protocols.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…A total of 591 implants were evaluated qualitatively: 348 installed with high insertion torque (. 25 Conclusion: The current review indicated that there is no significant difference in marginal bone resorption and implant failure rate between implants inserted with high or low insertion torque values. (Implant insertion torque, implant stability) to control implant healing and perform possible alterations in the treatment plan as a delayed load or progressive load protocols.…”
mentioning
confidence: 74%
“…Statistically higher early osseointegration rate (%BIC) at 2 weeks after implant insertion (in dog) was demonstrated by Campos et al 25 in implants inserted in undersized bone sites (median torque value of 70 N/cm) compared with implants inserted in oversized bone sites with lower torque insertion values (median value of 15 N/cm).…”
Section: Berardini Et Almentioning
confidence: 85%
“…In partial agreement, Campos et al . found that although the BIC was not affected, adequate drilling to achieve passive implantation outperformed over‐/under‐drilling by means of the bone area fraction occupied . Hence, clinical outcomes echo the uncertain impact high IT might have on peri‐implant bone loss compared with low IT.…”
Section: Excess Of Implant Torque On Bone Healingmentioning
confidence: 99%
“…70 In partial agreement, Campos et al found that although the BIC was not affected, adequate drilling to achieve passive implantation outperformed over-/under-drilling by means of the bone area fraction occupied. 71 Hence, clinical outcomes echo the uncertain impact high IT might have on peri-implant bone loss compared with low IT. Future research are currently investigating alternative strategies including the application of osseodensification protocols, 72 lasers, 73,74 or ultrasound tools [75][76][77][78] to enhance osseointegration.…”
Section: Implant Outcomes Under High and Low Implant Torquementioning
confidence: 99%
“…Alternative methods to better retain immobility after surgical placement of conventionally designed dental implants have been suggested (Martinez et al., ), including under‐preparation in diameter of an osteotomy, or the placement of a tapered implant into a cylindrical osteotomy, thereby compressing the cortical bone coronally (O'Sullivan et al., ). Several in vitro studies show that the relative gain of under‐preparation in terms of increased insertion torque or RFA values can be increased by 50%–100%, dependent on the discrepancy between the osteotomy and implant body diameters (Campos et al., ). In contrast, the comparative studies in Table describe the differences between the tapered versus non‐tapered designs up to maximum 10% at baseline in terms of implant insertion torque (O'Sullivan, Sennerby & Meredith, ; Kielbassa Kielbasa , Park et al., ; Torroella‐Saura et al., ; Stanford et al., ) or RFA values (Friberg et al., ; Kim, Lee, Lee & Yi, ; Markovic et al., ; McCullough & Klokkevold, ; O'Sullivan, Sennerby, Jagger & Meredith, ; Östman, Hellman & Sennerby, ; Park et al., ; Simmons et al., ; Waechter et al., ).…”
Section: Discussionmentioning
confidence: 99%